Quality Characteristics of shortbread Biscuit Fortified with Fermented Jack bean Flour - Ogori Akama Friday; FF Ajayi; OA Folorunsho; AF Ogori (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
Biscuit are usually produced from wheat flour, increasing cost and limited supply of wheat demand that attention be given to the application of indigenous grains to totally or partially replace wheat in bakery products. This study evaluated the effect of substituted fermented jack bean fl our (FJF) on wheat flour on proximate, mineral, physical and sensory properties of shortbread biscuit (SBB). Jack beans were soaked in water (6 h), de-hulled, re-soaked (12 h), sundried (3 days), oven-dried (55 °C, 24 h), milled, sieved and packaged for further processing. Shortbread biscuits (SBB) were produced using different levels of wheat flour substituted with FJF in 10% and 20% and using wheat fl our as control. Sensory evaluation of the biscuits was carried out using 5 point hedonic scale. The data obtained during the study was analyzed statistically using analysis of variance. Proximate composition, mineral, physical characteristics and sensory properties of the biscuit samples were determined. Moisture, crude protein, crude fibre, fat, ash and carbohydrate of the SBB ranged from 6.85-8.77, 8.41-10.17, 1.58-2.14, 18.39-19.42, 1.81-2.11 and 59.49-61.51%, respectively. Addition of FJF significantly increased the Ca (0.11 %), P (6.38 %), Mg (0.18%), Fe (2.29 %) and Mg (2.18 %) of the SBB compared to values obtained from 100% wheat flour. SBB with 20% FJF had the highest spread factor and spread ratio of 5.73 and 6.62, while SBB with 10% FJF had the least value. Sensory evaluation showed that SBB with 10 % FJF was preferred in terms of fl avour, mouth feel and overall acceptability. It was concluded that substitution of FJF into wheat flour gave the biscuit with the best overall quality acceptability.